1998
DOI: 10.1007/s004170050112
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of primary glaucoma triple procedure with adjunctive 5-fluorouracil

Abstract: The use of low-dose subconjunctival 5-FU (mean dosage of 24.8 mg in 5.0 +/- 1.3 injections) as an adjunct did not significantly improve the long-term filtration outcome of PGTP in POAG patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…25 Although long-term studies of phacotrabeculectomy with MMC report a mean pressure drop of 34% (to a mean IOP of 15 mm Hg) with MMC 2,26 and a pressure drop of 25% to 16 mm Hg with 5-fluorouracil, 27 these pressure levels were only achieved with the addition of a mean 1.0 medication per eye. We achieved a mean 33.2% pressure drop to a mean IOP of 16 mm Hg with virtually no medications (0.1 G 0.5).…”
Section: Discussionmentioning
confidence: 99%
“…25 Although long-term studies of phacotrabeculectomy with MMC report a mean pressure drop of 34% (to a mean IOP of 15 mm Hg) with MMC 2,26 and a pressure drop of 25% to 16 mm Hg with 5-fluorouracil, 27 these pressure levels were only achieved with the addition of a mean 1.0 medication per eye. We achieved a mean 33.2% pressure drop to a mean IOP of 16 mm Hg with virtually no medications (0.1 G 0.5).…”
Section: Discussionmentioning
confidence: 99%
“…Histologic examination of MMC-treated drainage blebs showed that the overlying treated area was virtually devoid of fibroblasts [45]. The clinical effect of the antimetabolites MMC and 5-FU has been well documented in many studies [3,7,42]. Many other antiproliferatives, such as mithramycin, daunorubicin and bleomycin [29], have been mainly investigated for in vitro use.…”
Section: Discussionmentioning
confidence: 99%
“…Although these agents may inhibit fibrosis and increase the success rate of surgery [4,7,8], highrisk patients with a history of long-term medication use or those who take multiple IOP-lowering medications or who have severe inflammation still show poor long-term surgical outcome [9]. In addition, administration of these antimetabolites can cause serious complications such as corneal decompensation, bleb leakage, hypotonous maculopathy, retinal bleeding, ciliary toxicity, and infective endophthalmitis [10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%